1987
DOI: 10.1037/0022-0167.34.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Use of structural equation modeling in counseling psychology research.

Abstract: Structural equation modeling (multivariate analysis with latent variables, also called causal modeling or covariance structure analysis) is a valuable methodological tool for use in counseling psychology research. Essentially the broad framework that subsumes many well-known procedures (e.g., multiple linear regression, factor analysis, path analysis), structural equation modeling allows for analysis of causal patterns among unobserved variables represented by multiple measures. It permits testing of causal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
141
0
8

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(149 citation statements)
references
References 51 publications
0
141
0
8
Order By: Relevance
“…Bunu gerçekleştirmek için atılacak en önemli adımlardan biri, ölçek geliştirme sürecinde izlenen aşamaların belirlenmesi, var olan durumun ve eksikliklerin ortaya konulması ve böylece ölçek geliştirme konusunda yapılan araştırmaların ayrıntılı olarak irdelenmesi olabilir. Bu konu ile ilgili olarak alan yazında yurt dışında yapılan çalışmalar incelendiğinde, sınırlı sayıda yapılan bu çalışmaların çoğunlukla tek bir dergiye odaklandığı, sınırlı konuların ve istatistik tekniklerin incelendiği ve bulguların çoğunlukla nicel tekniklerle yorumlandığı görülmektedir (Dawis, 1987;Fassinger, 1987;Kahn, 2006;Tinsley ve Tinsley, 1987;Worthington ve Whittaker, 2006). Örneğin, Tinsley ve Tinsley (1987) ve Kahn (2006) bir dergideki yayınlarda sadece faktör analizine odaklanırken; Martens (2005) ve Quintana & Maxwell (1999) aynı dergide yapısal eşitlik modeline odaklanarak genel bir değerlendirme sunmaktadır.…”
Section: Introductionunclassified
“…Bunu gerçekleştirmek için atılacak en önemli adımlardan biri, ölçek geliştirme sürecinde izlenen aşamaların belirlenmesi, var olan durumun ve eksikliklerin ortaya konulması ve böylece ölçek geliştirme konusunda yapılan araştırmaların ayrıntılı olarak irdelenmesi olabilir. Bu konu ile ilgili olarak alan yazında yurt dışında yapılan çalışmalar incelendiğinde, sınırlı sayıda yapılan bu çalışmaların çoğunlukla tek bir dergiye odaklandığı, sınırlı konuların ve istatistik tekniklerin incelendiği ve bulguların çoğunlukla nicel tekniklerle yorumlandığı görülmektedir (Dawis, 1987;Fassinger, 1987;Kahn, 2006;Tinsley ve Tinsley, 1987;Worthington ve Whittaker, 2006). Örneğin, Tinsley ve Tinsley (1987) ve Kahn (2006) bir dergideki yayınlarda sadece faktör analizine odaklanırken; Martens (2005) ve Quintana & Maxwell (1999) aynı dergide yapısal eşitlik modeline odaklanarak genel bir değerlendirme sunmaktadır.…”
Section: Introductionunclassified
“…The observed significant chi-square result indicated that the hypothesized model and the sample data were significantly different. However, the chi-square statistic is frequently significant since the test statistic is quite strict (Fassinger, 1987;Joreskog, 1969). Because of this, other indices are often considered since a relatively good t1t may be evident in spite of a significant chi-square value.…”
Section: Confirmatory Factor Analysesmentioning
confidence: 99%
“…The chi-square analysis often results in statistical significance for large samples, and consequently, it is not taken as an indicator of poor fit in practical terms (Bentler, 1990;Fassinger, 1987). More important for our purposes were the results from the other indices.…”
Section: Factor Analysesmentioning
confidence: 98%